Fusion of a Novel Native Signal Peptide Enhanced the Secretion and Solubility of Bioactive Human Interferon Gamma Glycoproteins in Nicotiana benthamiana Using the Bamboo Mosaic Virus-Based Expression System - Jiang, Min-Chao; Hu, Chung-Chi; Hsu, Wei-Li; Hsu, Tsui-Ling; Lin, Na-Sheng; Hsu, Yau-Heiu (Frontiers in Plant Science, 2020)
Plant viruses may serve as expression vectors for the efficient production of pharmaceutical proteins in plants. However, the downstream processing and post-translational modifications of the target proteins remain the major challenges. We have previously developed an expression system derived from Bamboo mosaic virus (BaMV), designated pKB19, and demonstrated its applicability for the production of human mature interferon gamma (mIFNγ) in Nicotiana benthamiana. In this study, we aimed to enhance the yields of soluble and secreted mIFNγ through the incorporation of various plant-derived signal peptides. Furthermore, we analyzed the glycosylation patterns and the biological activity of the mIFNγ expressed by the improved pKB19 expression system in N. benthamiana. The results revealed that the fusion of a native N. benthamiana extensin secretory signal (SSExt) to the N-terminal of mIFNγ (designated SSExtmIFNγ) led to the highest accumulation level of protein in intracellular (IC) or apoplast washing fluid (AWF) fractions of N. benthamiana leaf tissues. The addition of 10 units of ‘Ser-Pro’ motifs of hydroxyproline-O-glycosylated peptides (HypGPs) at the C-terminal end of SSExtmIFNγ (designated SSExtmIFNγ(SP)10) increased the solubility to nearly 2.7- and 1.5-fold higher than those of mIFNγ and SSExtmIFNγ, respectively. The purified soluble SSExtmIFNγ(SP)10 protein was glycosylated with abundant complex-type N-glycans attached to residues N56 and N128, and exhibited biological activity against Sindbis virus and Influenza virus replication in human cell culture systems. In addition, suspension cell cultures were established from transgenic N. benthamiana, which produced secreted SSExtmIFNγ(SP)10 protein feasible for downstream processing. These results demonstrate the applicability of the BaMV-based vector systems as a useful alternative for the production of therapeutic proteins, through the incorporation of appropriate fusion tags.